2016
DOI: 10.3748/wjg.v22.i33.7613
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic insights of rapid liver regeneration after associating liver partition and portal vein ligation for stage hepatectomy

Abstract: AIMTo highlight the potential mechanisms of regeneration in the Associating Liver Partition and Portal vein ligation for Stage hepatectomy models (clinical and experimental) that could unlock the myth behind the extraordinary capability of the liver for regeneration, which would help in designing new therapeutic options for the regenerative drive in difficult setup, such as chronic liver diseases. Associating Liver Partition and Portal vein ligation for Stage hepatectomy has been recently advocated to induce r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 80 publications
0
22
0
1
Order By: Relevance
“…Moreover, LSEC are also involved in modulating vascular tone and portal flow, which can also be a crucial trigger for liver regeneration after partial hepatectomy. 4 As the authors demonstrated a clear interaction between PLT and LSEC, it would be of interest to know whether this interaction had an effect on portal flow, as demonstrated in previous studies. 5 Finally, the authors modulated PLT count by the intravenous injection of platelet-depleting antibodies.VWF was, however, the only PLT-associated factor examined.…”
Section: The Role Of Platelets On Regenerating Liver: Thoughts Beyondmentioning
confidence: 69%
See 1 more Smart Citation
“…Moreover, LSEC are also involved in modulating vascular tone and portal flow, which can also be a crucial trigger for liver regeneration after partial hepatectomy. 4 As the authors demonstrated a clear interaction between PLT and LSEC, it would be of interest to know whether this interaction had an effect on portal flow, as demonstrated in previous studies. 5 Finally, the authors modulated PLT count by the intravenous injection of platelet-depleting antibodies.VWF was, however, the only PLT-associated factor examined.…”
Section: The Role Of Platelets On Regenerating Liver: Thoughts Beyondmentioning
confidence: 69%
“…Additional data on PLT function in terms of PLT-mediated molecules could shed additional light on understanding the mechanism of liver regeneration following hepatectomy. 2,4,5 Focusing more on the function of remnant liver and the activity rather than the expression of different cells could help our understanding on the liver regeneration. REFERENCES 1.…”
mentioning
confidence: 99%
“…In addition, peri‐operative (portal vein embolization) and intra‐operative (two‐stage hepatectomy, associating liver partitioning with portal vein ligation for staged hepatectomy (ALPPS), etc.) advances have also been critical in expanding the number of patients with CLM who are candidates for surgery , . Despite these advances, many patients with CLM still present with unresectable disease that is not amenable to surgical resection.…”
Section: Discussionmentioning
confidence: 99%
“…It is known [5][6][7][8][9] that 25% is the minimum volume of hepatic remnant for adequate recovery in patients with morphologically intact liver. In the presence of druginduced damage (chemotherapy) or with background liver diseases (cirrhosis, fibrosis, hepatosis), at least 40% of the initial liver volume is needed to remain.…”
Section: Introductionmentioning
confidence: 99%